Study on The Nurul Quran Method at The Syakirin Center of Al-Qur’an Education - Wahid, Abd.; Mahmud, Nursyahindah Binti; Asnawiyah, Asnawiyah; Nazaryani, Nazaryani (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Every believer is obligated to possess the ability to read the Quran proficiently. This obligation extends not only to adults but is also encouraged from a young age, ensuring that children learn the sacred verses of the Quran. The significance of this mandate is earnestly acknowledged by the Youth Department of the Pan-Malaysian Islamic Party (PAS), which has established several renowned Quranic Education Centers throughout Malaysia. These educational centers have received widespread recognition and are considered pioneers in the establishment of Quranic Education Centers (TPA). Over the past half-century since its inception, TPA has continued to evolve, employing a teaching methodology known as the "Nurul Quran Method." This article aims to assess the effectiveness of the Nurul Quran Method in the Quranic learning process at TPA Syakirin. Additionally, the article explores the challenges faced by teachers and administrators at TPA Syakirin in their efforts to enhance students' abilities within the institution. This study adopts a qualitative approach, utilizing methods such as observation, interviews, and documentation for data collection. The research findings indicate that the learning process using the Nurul Quran Method proceeds smoothly. This method incorporates elements of "learning through play" and various other creative techniques. One of the key strengths of TPA Syakirin lies in its utilization of a distinctive teaching methodology, not only in Malaysia but also from Quranic education institutions in other countries across Southeast Asia.